Exposure to ACE inhibitors prior to the onset of scleroderma renal crisis-results from the international scleroderma renal crisis survey - (:unkn) unknown (W.B. Saunders, 2014)
Objective: To determine whether exposure to angiotensin-converting enzyme (ACE) inhibitors prior to the onset of scleroderma renal crisis (SRC) leads to worse outcomes of SRC. Methods: Prospective cohort study of incident SRC subjects. The exposure of interest was ACE inhibitors prior to the onset of SRC. The outcomes of interest were death or dialysis during the first year after the onset of SRC. Results: A total of 87 subjects with incident SRC were identified and 1-year follow-up data were obtained in 75 (86%) subjects. Overall, 27 (36%) subjects died within the first year and an additional 19 (25%) remained on dialysis 1 year after the onset of SRC. In adjusted analyses, exposure to ACE inhibitors prior to the onset of SRC was associated with an increased risk of death (hazard ratio 2.42, 95% CI 1.02, 5.75, p < 0.05 in the primary analysis and 2.17, 95% CI 0.88, 5.33, p = 0.09 after post-hoc adjustment for pre-existing hypertension). Conclusion: Overall, the 1-year outcomes of SRC were poor. Prior exposure to ACE inhibitors was associated with an increased risk of death after the onset of SRC, although there was uncertainty around the magnitude of the risk and the possibility of residual confounding could not be ruled out. Further studies will be needed to confirm these findings. © 2014 Elsevier Inc.
Keywords: ACE inhibitors; Scleroderma; Scleroderma renal crisis